(3fXQjI GdEMJeGdGJ (B:s (3eHGOF hJWHjbGJ (B/s - (3eUWai, YHO GdMajXs ((3GdLRGFQ(B: s (3OjhGf GdeWHhYGJ GdLGeYjI(B, s, 2004)
(3GdaQGZ GdEMJeGdj(B- (3eHGOF GdJMdjd GdJhGabj(B- (3WQb JYjjf GdEMJeGdGJ(B- (3GdEMJeGd GdTQWj(B- (3GdMhGOK hGdJcQGQGJ GdeSJbdI(B- (3GdEMJeGdGJ GdYThGFjI hMjOI GdHYO(B- (3eejRGJ YOOjI ddeJMhdGJ GdYThGFjI hMjOI GdHYO(B- (3GdJhRjYGJ GdEMJeGdjI GdefbWYI GdCSGSjI(B- (3GdJhRjYGJ GdEMJeGdjI GdeSJeQI GdCSGSjI(B.s
Keywords: (3GdEMJeGdGJs; (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdQjGVjGJs